Disability and Labor Market Exclusion: Evidence from Indonesia - Dewi, Rika Kumala; Al Izzati, Ridho; Suryahadi, Asep (The Indonesian Forestry Certification Cooperation, 2022)
In accordance with the Sustainable Development Goals (SDG) No. 8 on Decent Work and Economic Growth, people with and without disabilities have equal rights to access decent and productive jobs. Furthermore, the fulfillment of the righths of disabled people to decent jobs will help to achieve SDG No. 10 on Reduced Inequality. However, in reality, there are pervasive and persistent barriers for people with disabilities to access the labor market. Using Indonesian data, this study examines labor market exclusion among people with disabilities and identifies the challenges that they face. Our findings on labor force participation, unemployment status, employment status as self-employed or employee in the formal sector, and feeling discouraged to enter the labor market indicate that being disabled is associated with a greater probability of being excluded from the labor market and of feeling discouraged, particularly among unemployed individuals. Various factors, including individual level factors, environmental supports, and government policies, affect the inclusion of disabled people in the labor market. These imply that the governments need to strengthen the affirmative actions and promote disabled people’s capabilities to increase employment opportunities for them. Important measures to improve labor market inclusion among people with disabilities are ensuring that their employment quota is enforced and protecting their rights to access employment, increasing their access to high-quality formal and non-formal education, and increasing their access to credit.